2007
DOI: 10.1007/s00270-007-9136-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Elective Bilateral Versus Unilateral Femoral Arterial Puncture for Uterine Artery Embolization

Abstract: The purpose of this study was to assess the effect of elective bilateral femoral arterial punctures for uterine artery embolization (UAE) of symptomatic fibroids on fluoroscopy and procedural time, patient dose, and ease of procedure. We conducted a prospective study of UAE with either the intention to catheterize both uterine arteries using a single femoral puncture (n = 12) or elective bilateral arterial punctures from the outset (n = 12). The same two operators undertook each case. Main outcome measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…The fact that both Bratby et al and Costantino et al found no significant difference but only a slight tendency toward lower radiation exposure for the bilateral approach is probably mainly attributable to the small sample sizes investigated [24,27]. However, in both studies, fluoroscopy time at least was significantly shorter.…”
Section: Bilateral Accessmentioning
confidence: 49%
See 1 more Smart Citation
“…The fact that both Bratby et al and Costantino et al found no significant difference but only a slight tendency toward lower radiation exposure for the bilateral approach is probably mainly attributable to the small sample sizes investigated [24,27]. However, in both studies, fluoroscopy time at least was significantly shorter.…”
Section: Bilateral Accessmentioning
confidence: 49%
“…The measures they used to reduce patient dose were simple and should be known to all interventional radiologists: optimized sourceimage and object-image distances, avoidance of magnification, tight collimation, reduction of image frequency during angiographic runs to one image every other second, and documentation of the angiographic endpoint using lastimage-hold (LIH) instead of another angiographic run. Many studies on radiation exposure during UAE followed and are compiled in Table 3 [16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduction of fluoroscopy time can be achieved by performing UFE with bilateral access and parallel instead of sequential embolisation [11,12]. The combination of bilateral access and measures to reduce radiation exposure is also applicable during perioperative temporary balloon occlusion of the internal iliac arteries as a prophylaxis in cesarean section in pregnant women at risk for peri-and post-partum hemorrhage [13].…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed fluoroscopy with a low frame rate and careful coning should be used as the mainstay of intra-procedural imaging and angiographic runs should be avoided as much as possible (Bratby and Belli 2008;Braude et al 2000;Goodwin et al 2003). Bilateral femoral arterial puncture technique has been shown to reduce fluoroscopy time and catheter manipulation compared to a unilateral access technique, with a 25 % reduction in simulated dose (Bratby et al 2007). The same study demonstrated that the overall fluoroscopy time and patient dose are generally very low.…”
Section: Radiation Protectionmentioning
confidence: 97%